VD_FINDINFO Jug / 2012 / 180 vom 27. Februar 2012 - VD Tribunal cantonal (2012)
CONTRAINTEDROIT PÉNAL, TENTATIVEDROIT PÉNAL, ACQUITTEMENT, FRAIS JUDICIAIRES, DÉPENS | 181 CP, 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH), 433 al. 1 CPP(CH)